2014
DOI: 10.1111/eva.12139
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization increases invasive knotweed success

Abstract: Hybridization is one of the fundamental mechanisms by which rapid evolution can occur in exotic species. If hybrids show increased vigour, this could significantly contribute to invasion success. Here, we compared the success of the two invasive knotweeds, Fallopia japonica and F. sachalinensis, and their hybrid, F. × bohemica, in competing against experimental communities of native plants. Using plant material from multiple clones of each taxon collected across a latitudinal gradient in Central Europe, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 67 publications
(128 reference statements)
3
63
0
1
Order By: Relevance
“…3). Also, the lowest number of significantly associated species for F. ×bohemica sites can in part confirm the observations of Parepa et al [30]. As far as the resident species is concerned, some studies have shown that one of the most frequent accompanying species to Fallopia spp.…”
Section: Impact Of Fallopia Complex Members On Resident Plant Speciessupporting
confidence: 87%
See 3 more Smart Citations
“…3). Also, the lowest number of significantly associated species for F. ×bohemica sites can in part confirm the observations of Parepa et al [30]. As far as the resident species is concerned, some studies have shown that one of the most frequent accompanying species to Fallopia spp.…”
Section: Impact Of Fallopia Complex Members On Resident Plant Speciessupporting
confidence: 87%
“…Nevertheless, it is apparent that the three Fallopia taxa influence the co-occurring plant composition in a different way or that the effect can be manifested at a different time in relation to the history of invasion. 30 plots. This is a relatively small number of species, especially in habitats as species-rich as riparian zones.…”
Section: Impact Of Fallopia Complex Members On Resident Plant Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no general patterns have been found and the topic is contrarily discussed (e.g. [37] [58] [59]). …”
Section: Discussionmentioning
confidence: 99%